Quantum Teaching in An Islamic Perspective - Zohriah, Anis; Fauzi, Anis; Fazrurrakhman Al Farisi; Asyiah, Euis (Jurnal Kependidikan Islam, 2024)
This article examines Quantum Teaching according to Islamic Education, by discussing the methodology used in the design, presentation, and facilities used in teaching. This study was conducted to contribute thoughts from the author so that it can be input material to see the possibility of its application in efforts to improve and develop Islamic Education Institutions. This article uses a bibliographical approach where the data comes from various sources. This study shows that there have been several improvements in Islamic education teaching methods in modern times. The purpose of writing this article is to produce Islamic Education graduates who develop all their potential and have a positive attitude in Islamic Education Institutions or lecturers who teach using the Islamic education method. Quantum Teaching as well as preparing graduates who have broad insight, emotional intelligence, skills, and have self-confidence and are able to compete in the globalization era.